2013
DOI: 10.1074/jbc.a112.357707
|View full text |Cite
|
Sign up to set email alerts
|

δ-Tocopherol reduces lipid accumulation in Niemann-Pick type C1 and Wolman cholesterol storage disorders.

Abstract: Authors are urged to introduce these corrections into any reprints they distribute. Secondary (abstract) services are urged to carry notice of these corrections as prominently as they carried the original abstracts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(31 citation statements)
references
References 0 publications
0
31
0
Order By: Relevance
“…Generally, a characteristic associated with the disease is exploited to develop a cell-based assay for a modern phenotypic screen (Figure 2B). Compounds are then screened in the phenotypic assay to identify active lead compounds that ameliorate the disease phenotype, exemplified by selectively killing cancer cells [19], eliminating pathogens in culture [20], or reducing lysosomal cholesterol accumulation in Niemann Pick disease type C patient cells [21]. …”
Section: Phenotypic Screening In Drug Discoverymentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, a characteristic associated with the disease is exploited to develop a cell-based assay for a modern phenotypic screen (Figure 2B). Compounds are then screened in the phenotypic assay to identify active lead compounds that ameliorate the disease phenotype, exemplified by selectively killing cancer cells [19], eliminating pathogens in culture [20], or reducing lysosomal cholesterol accumulation in Niemann Pick disease type C patient cells [21]. …”
Section: Phenotypic Screening In Drug Discoverymentioning
confidence: 99%
“…For example, expression of long CAG trinucleotide repeats in the mutant HTT gene in Huntington’s disease is cytotoxic and results in cell death, which can be detected by a cell viability assay [43,50]. In Niemann Pick disease type C, lysosomal cholesterol accumulation in patient cells is a characteristic disease phenotype that can be measured by a filipin staining assay [21,51]. …”
Section: Cell-based Phenotypic Assaysmentioning
confidence: 99%
“…This was also found to be the case for the primary sphingomyelin storage disorder Niemann-Pick type A. However, the authors found no difference in lysosomal Ca 2 + content between wild-type and NPC1 null cells, despite this being widely reported [38][39][40][41]. The authors found that treating NPC1 null cells with MLSA1 led to an improvement in phenotypes.…”
Section: Trpml1 In Diseasementioning
confidence: 82%
“…104 Lysosomal exocytosis has also been documented in MSD and MPS type IIIA via overexpression of transcription factor EB (TFEB), 105 or by using δ-tocopherol, as shown for NPC and Wolman diseases. 106 Moreover, δ-tocopherol has been shown to reduce lipid accumulation in LSD cell models of Batten, Fabry, Farber, Sanfilippo type B, Tay-Sachs, and Niemann-Pick disease type A. 106 Although certainly valuable, most these approaches are suboptimal, particularly for neurological symptoms.…”
Section: Clinical and Experimental Treatmentsmentioning
confidence: 99%
“…106 Moreover, δ-tocopherol has been shown to reduce lipid accumulation in LSD cell models of Batten, Fabry, Farber, Sanfilippo type B, Tay-Sachs, and Niemann-Pick disease type A. 106 Although certainly valuable, most these approaches are suboptimal, particularly for neurological symptoms. Hence, there is a compelling need for approaches to more effectively treat these diseases.…”
Section: Clinical and Experimental Treatmentsmentioning
confidence: 99%